Primary prevention of stroke and cardiovascular disease in the community (PREVENTS): Methodology of a health wellness coaching intervention to reduce stroke and cardiovascular disease risk, a randomized clinical trial. Issue 2 (February 2018) - Mahon, Susan; Krishnamurthi, Rita; Vandal, Alain; Witt, Emma; Barker-Collo, Suzanne; Parmar, Priya; Theadom, Alice; Barber, Alan; Arroll, Bruce; Rush, Elaine; Elder, Hinemoa; Dyer, Jesse; et al.
Rationale: Stroke is a major cause of death and disability worldwide, yet 80% of strokes can be prevented through modifications of risk factors and lifestyle and by medication. While management strategies for primary stroke prevention in high cardiovascular disease risk individuals are well established, they are underutilized and existing practice of primary stroke prevention are inadequate. Behavioral interventions are emerging as highly promising strategies to improve cardiovascular disease risk factor management. Health Wellness Coaching is an innovative, patient-focused and cost-effective, multidimensional psychological intervention designed to motivate participants to adhere to recommended medication and lifestyle changes and has been shown to improve health and enhance well-being. Aims and/or hypothesis: To determine the effectiveness of Health Wellness Coaching for primary stroke prevention in an ethnically diverse sample including Māori, Pacific Island, New Zealand European and Asian participants. Design: A parallel, prospective, randomized, open-treatment, single-blinded end-point trial. Participants include 320 adults with absolute five-year cardiovascular disease risk ≥ 10%, calculated using the PREDICT web-based clinical tool. Randomization will be to Health Wellness Coaching or usual care groups. Participants randomized to Health Wellness Coaching will receive 15 coaching sessions over nine months. Study outcomes: A substantial relative risk reduction of five-year cardiovascular disease risk at nine months post-randomization, which is defined as 10% relative risk reduction among those at moderate five-year cardiovascular disease risk (10–15%) and 25% among those at high risk (>15%). Discussion: This clinical trial will determine whether Health Wellness Coaching is an effective intervention for reducing modifiable risk factors, and hence decrease the risk of stroke and cardiovascular disease.